Aberrant Chloride Intracellular Channel 4 Expression Is Associated With Adverse Outcome in Cytogenetically Normal Acute Myeloid Leukemia - Huang, Sai; Huang, Zhi; Chen, Ping; Feng, Cong (Frontiers in Oncology, 2020)
Background and Methods: Acute myeloid leukemia (AML), which starts in the bone marrow, is a group of hematopoietic stem cell disorders. Chloride intracellular channel 4 (CLIC4) is regulated by p53, c-Myc, and TGF-β. It induces the NF-κB-dependent activation of HIF (hypoxia-inducible factor) and participates in tumor growth through its microenvironmental function. However, its prognostic value in AML remains unclear, as well as its co-expression biomarkers. In this study, we evaluated the prognostic significance of CLIC4 expression using two independent large cohorts of cytogenetically normal AML (CN-AML) patients. Multivariable analysis and multi-omics analysis with weighted correlation network analysis (WGCNA) in the CN-AML group were also presented. Based on CLIC4 and its related genes, microRNA–target gene interaction network analysis and downstream gene ontology analysis were performed to unveil the complex functions behind CLIC4. Results: We demonstrated that the overexpression of CLIC4 was notably associated with unfavorable outcome in the two independent cohorts of CN-AML patients [overall survival (OS) and event-free survival (EFS): P < 0.0001, n = 185; OS: P = 0.016, n = 232], as well as in the European LeukemiaNet (ELN) Intermediate-I group (OS: P = 0.015, EFS: P = 0.012, n = 115), the National Comprehensive Cancer Network Intermediate Risk AML group (OS and EFS: P < 0.0001, n = 225), and the non-M3 AML group (OS and EFS: P < 0.0001, n = 435). Multivariable analysis further validated CLIC4 as a high-risk factor in the CN-AML group. Multi-omics analysis presented the overexpression of CLIC4 as associated with the co-expression of the different gene sets in leukemia, up/downregulation of the immune-related pathways, dysregulation of microRNAs, and hypermethylation around the CpG islands, in open sea regions, and in different gene structural fragments including TSS1500, gene body, 5′UTR region, 3′UTR region, and the first exon. By further performing WGCNA on multi-omics data, certain biomarkers that are co-expressed with CLIC4 were also unveiled. Conclusion: We demonstrated that CLIC4 is a novel, potential unfavorable prognosticator and therapeutic target for CN-AML. As having a key role in CN-AML, the interactions between CLIC4 and other genomics and transcriptomics data were confirmed by performing microRNA–target gene interaction network analysis and gene ontology enrichment analysis. The experimental result provides evidence for the clinical strategy selection of CN-AML patients.